PENGARUH BRAND PERSONALITY DAN BRAND LOYALTY TERHADAP KEPUTUSAN PEMBELIAN MEREK FASHION INDONESIA ERIGO STORE DI SURABAYA - Ainur Rosi; Yurilla Endah Muliatie (Jurnal Ekonomi, Bisnis dan Social, 2024)
The Effects of Brand Personality and Brand Loyalty on Purchasing Decisions of Fashion Brands in Indonesia Erigo Store Surabaya, 2023.This study aims to identify the effect of brand personality and brand loyalty on purchasing decisions for the Indonesian fashion brand Erigo Store. The method used in this study is a quantitative method with multiple linear regression analysis techniques. This research was conducted on respondents who have experience in using Indonesian Erigo Store fashion products.Data was collected using a questionnaire distributed via social media. The sample used in this study was 100 respondents. The data obtained was then processed and analyzed using SPSS software version 25. The results showed that brand personality and loyalty significantly influence purchasing decisions for the Indonesian fashion brand Erigo Store. In addition, the results of the analysis show that the dimension of brand personality that has the most influence on purchasing decisions is the dimension of sincerity, while the dimension of brand loyalty that has the most influence is the indicator of brand trust.This research has an essential contribution to Erigo Store in developing its brand and increasing customer satisfaction. The results of this study can also be a reference for future researchers in developing research in the field of brand marketing.